2016
DOI: 10.1097/wco.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Novel MRI and PET markers of neuroinflammation in multiple sclerosis

Abstract: Purpose of reviewGadolinium-enhancement depicts BBB disruption associated with new inflammatory MRI lesions in MS and is widely used for diagnosis and therapeutic monitoring. However, earlier and more specific markers of inflammation are urgently needed.  TSPO PET shows that increased microglia activation is present in both normal appearing tissue and MS specific lesions and is related to disease severity and progression  A wide range of novel PET markers will give us unique insights in the pathophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Gadolinium enhancement in MS lesions is preceded and outlasted by infiltration with immune cells. This has been demonstrated in MS patients with positron emission tomography (PET) imaging studies using radioactive ligands for the 18-kDa translocator protein (TSPO) ( 80 ), and with MRI of ultra-small iron-oxide particles that were injected peripherally and detected in activated monocytes/macrophages infiltrating the lesions ( 81 ). These imaging results are consistent with histological studies indicating that significant inflammatory activity occurs behind a closed BBB ( 82 ).…”
Section: Detecting Chronic Inflammation In Ms Patientsmentioning
confidence: 99%
“…Gadolinium enhancement in MS lesions is preceded and outlasted by infiltration with immune cells. This has been demonstrated in MS patients with positron emission tomography (PET) imaging studies using radioactive ligands for the 18-kDa translocator protein (TSPO) ( 80 ), and with MRI of ultra-small iron-oxide particles that were injected peripherally and detected in activated monocytes/macrophages infiltrating the lesions ( 81 ). These imaging results are consistent with histological studies indicating that significant inflammatory activity occurs behind a closed BBB ( 82 ).…”
Section: Detecting Chronic Inflammation In Ms Patientsmentioning
confidence: 99%
“…Studies based on imaging with tracers for TSPO such as [ 11 C]PK11195 have been carried out in MS patients and in animal models [15]. It was demonstrated that [ 11 C]PK11195 PET can detect macrophage infiltration in acute demyelinated lesions and colocalizes with lesions detected by gadoliniumenhanced T1-weighted MRI [16,17]. More recently, a few studies in animal models of MS using new PET tracers for imaging of TSPO have been published, but further data in larger well-defined groups of MS patients are required to determine the value of PET imaging of TSPO expression for monitoring neuroinflammation in this population [18].…”
mentioning
confidence: 99%
“…11 C-JNJ-54173717, 11 C-A-740003, 11 C-GSK-1482160), 57,66,67 and some of them have been tested on animal models of MS. 57,66 These tracers might measure the activation of microglia and the associated release of inflammatory cytokines, and are expected to be tested soon in-vivo. 68…”
Section: Inflammatory Markersmentioning
confidence: 99%